2011
DOI: 10.3109/03014460.2011.591827
|View full text |Cite
|
Sign up to set email alerts
|

Parental and offspring adiposity associations: Insights from the 1958 British birth cohort

Abstract: Parent-offspring associations in BMI were not explained by offspring lifestyles, but varied over successive generations and by social class, suggesting that intergenerational transmission of adiposity at a population level is modifiable rather than immutable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 47 publications
4
40
0
Order By: Relevance
“…Women who selected that their child resembled an image of a larger body size had higher BMIs than those who selected a smaller body size. These findings agree with previous reports regarding parental BMI and child's weight status [25,26]. In addition to the relationship between mother's BMI and child's body shape, we explored additional variables that may influence child's weight status.…”
Section: Discussionsupporting
confidence: 79%
“…Women who selected that their child resembled an image of a larger body size had higher BMIs than those who selected a smaller body size. These findings agree with previous reports regarding parental BMI and child's weight status [25,26]. In addition to the relationship between mother's BMI and child's body shape, we explored additional variables that may influence child's weight status.…”
Section: Discussionsupporting
confidence: 79%
“…Intergenerational associations for adiposity are well established; offspring of obese parents have an elevated risk of overweight/obesity. Lifestyle and sociodemographic factors for offspring did not explain parent-offspring BMI associations; however, Power et al (85) have shown variations in the intergenerational association over successive generations and also by social class, which suggests that intergenerational transmission of adiposity at a population level is not immutable. Intergenerational transmission of adiposity may be due in part to greater nutrient transfer from obese mothers to the fetus, leading to permanent changes in appetite, metabolism, and other functions, as envisaged by the fetal origins hypothesis.…”
Section: Lifetime Growth Trajectories and Adult Diseasementioning
confidence: 80%
“…Parental weight has been shown to be a strong determinant of the adult offspring weight through pre-natal programming, genetic predisposition and shared environmental factors such as diet and physical activity [27][28][29][30]. A series of studies examining parentoffspring BMI associations within a 1958 British birth cohort reported that they (1) were maintained from child to mid-adulthood; (2) had strengthened over two generations; and (3) varied by socioeconomic origins rather than the lifestyle and socioeconomic position of adult offspring.…”
Section: Samplementioning
confidence: 99%